Analisis Hukum terhadap Perusakan Kertas Suara Pemilihan Umum - Mhd. Teguh Syuhada Lubis (Universitas Medan Area, 2020)
Democracy is a miracle or understanding that puts the foundations of togetherness and honesty and democracy make all people have their existence and becomes meaningful for society to maintain the diversity that does not divide people between the rich and poor. the strong with the weak. and the smart with fools. And democracy also does not recognize discrimination even if there is a difference in society and country and democracy gives similarities. This writing uses normative legal research methods (normative research) with descriptive-analytical research specifications that use secondary data. Data collection procedures are in the form of documentation of notes or quotations. a search of legal literature. books and others related to the identification of problems both offline and online which are then analyzed using the legislative approach through content analysis methods (content analysis method) with a focus on the issue of How is criminal liability for the perpetrators of the destruction of the ballot paper in legislative elections? From the results of the study note that criminal liability for the perpetrators of the destruction of the ballot paper in the legislative election is convicted in accordance with the provisions of the law that is passed and carried out by enforcing the regulations that have been made through the application of the criminal